2020
DOI: 10.1111/ced.14303
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in atopic eczema? An analysis of systematic reviews published in 2018. Part 1: prevention and topical therapies

Abstract: Summary This review is part of a series of annual updates that summarize the evidence base for atopic eczema (AE). The aim is to provide a succinct guide for clinicians on the key findings from 14 systematic reviews on the prevention and topical treatment of AE published or indexed in 2018. Various supplements, including long‐chain polyunsaturated fatty acids, vitamin D and the probiotic Lactobacillus rhamnosus GG, given prenatally and postnatally, have not been shown to prevent AE in infants, although mixed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although previous studies among patients with asthma or rheumatic disease have suggested associations between long-term use of oral corticosteroids and various adverse events (AEs), there are few studies of patients with AD, to our knowledge . In addition, existing studies about corticosteroid use among patients with AD were conducted to evaluate the safety concerns primarily about topical corticosteroids . Considering the frequent use of oral corticosteroids among adults with AD and the potential association between long-term use of oral corticosteroids and AEs, some of which are severe, there is a need to investigate the safety of the long-term use of oral corticosteroids among adults with AD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies among patients with asthma or rheumatic disease have suggested associations between long-term use of oral corticosteroids and various adverse events (AEs), there are few studies of patients with AD, to our knowledge . In addition, existing studies about corticosteroid use among patients with AD were conducted to evaluate the safety concerns primarily about topical corticosteroids . Considering the frequent use of oral corticosteroids among adults with AD and the potential association between long-term use of oral corticosteroids and AEs, some of which are severe, there is a need to investigate the safety of the long-term use of oral corticosteroids among adults with AD .…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 , 20 , 21 In addition, existing studies about corticosteroid use among patients with AD were conducted to evaluate the safety concerns primarily about topical corticosteroids. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Considering the frequent use of oral corticosteroids among adults with AD and the potential association between long-term use of oral corticosteroids and AEs, some of which are severe, there is a need to investigate the safety of the long-term use of oral corticosteroids among adults with AD. 6 , 30 , 31 Accordingly, we aimed to investigate the association between long-term use of oral corticosteroids and AEs among adult patients with AD in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 12 years, the Centre of Evidence-Based Dermatology (CEBD) has conducted annual updates of systematic reviews related to various aspects of eczema management [1][2][3] with a focus on critical appraisal, in order to inform clinical practice. Topics include epidemiology [4], disease mechanisms [5], risk factors [6,7], prevention [8], topical [3] and systemic therapies [2]. We use this comprehensive resource of appraised systematic reviews as the main evidence source for this article, supplemented by key randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 12 years, the Centre of Evidence-Based Dermatology (CEBD) has conducted annual updates of systematic reviews related to various aspects of eczema management [1–3] with a focus on critical appraisal, in order to inform clinical practice. Topics include epidemiology [4], disease mechanisms [5], risk factors [6,7], prevention [8], topical [3] and systemic therapies [2].…”
Section: Introductionmentioning
confidence: 99%